Mathematics in Physical Education: how mathematical skills help students understand and improve their physical performance - Sousa, Rodger Roberto Alves de; Borges, Francisléia dos Santos; Afonso, Lucas Rodrigues (Revista Interseção, 2025)
ABSTRACT This article highlights the importance of mathematics in physical education, emphasizing how mathematical skills can help students understand and improve their physical performance. Through a literature review, several areas were identified in which mathematics can be applied in physical education, such as statistical analysis of performance data, geometry in the construction of sports facilities, kinematics of body movements, and the use of technology for learning. In addition, the hypothesis that the application of mathematics can contribute to improving students' physical performance was evaluated, and the results indicated that the use of mathematical concepts can indeed contribute to a better understanding of technique and injury prevention. The proposed methodology includes the use of practical activities, with the aim of connecting mathematical concepts to the reality of sports and promoting interdisciplinary between mathematics and physical education. In conclusion, the study points to the importance of incorporating mathematics teaching in physical education in order to provide students with a more complete education and contribute to better performance in physical activities. Keywords: Mathematics. Physical Education. Physical Performance. Interdisciplinarity. Technology. RESUMO Este artigo destaca a importância da matemática na educação física, enfatizando como as habilidades matemáticas podem ajudar os alunos a entender e melhorar seu desempenho físico. Através de uma revisão da literatura, foram identificadas diversas áreas em que a matemática pode ser aplicada na educação física, tais como a análise estatística de dados de desempenho, a geometria na construção de instalações esportivas, a cinemática dos movimentos corporais, e o uso da tecnologia para o aprendizado. Além disso, a hipótese de que a aplicação da matemática pode contribuir para aprimorar o desempenho físico dos alunos foi avaliada, e os resultados indicaram que a utilização de conceitos matemáticos pode, de fato, contribuir para uma melhor compreensão da técnica e prevenção de lesões. A metodologia proposta inclui a utilização de atividades práticas, com o objetivo de conectar os conceitos matemáticos à realidade dos esportes e promover a interdisciplinaridade entre matemática e educação física. Em conclusão, o estudo aponta para a importância de se incorporar o ensino de matemática na educação física, a fim de proporcionar aos alunos uma educação mais completa e contribuir para um melhor desempenho em atividades físicas. Palavras-chave: Matemática. Educação Física. Desempenho Físico. Interdisciplinaridade. Tecnologia.